MKAS : A modular knockout ATM switch - Waqas, Muhammad; Seman, Kamaruzzaman; Nik Yusof, Nik Mohd. KamiI (2000)
Simple Knockout Switch [11 exhibits excellent traffic performance (cell loss, cell delay and maximum throughput etc.) under uniform as well as non-uniform traffic patterns (2-6). But being a single stage, its hardware complexity is directly proportional to the switch size N. This problem may bind its implementation for largescale requirements because of the technological and physical constraints of packaging (e. g. chip or board size). Here, we are proposing a two-stage Modular Knockout ATM Switch architecture, which is extendable to large-scale switch sizes without sacrificing any significant decrease in switch performance. The concept of Generalised Knockout Principle in conjunction with Simple Knockout Principle has been utilised to filter, route and resolve the output contention problems in distributed fashion. Using distributed address filtration and shared concentration techniques simplifies the switch functions and reduces the switch complexity to large extent in terms of filters, switching elements and input output interconnection wires.